Household Decision-making about Delivery in Health Facilities: Evidence from Tanzania - Danforth, EJ; Kruk, ME; Rockers, PC; Mbaruku, G; Galea, S (Journal of Health, Population and Nutrition, 2009)
This study investigated how partners' perceptions of the healthcare system influence decisions about delivery-location in low-resource settings. A multistage population-representative sample was used in Kasulu district, Tanzania, to identify women who had given birth in the last five years and their partners. Of 826 couples in analysis, 506 (61.3%) of the women delivered in the home. In multivariate analysis, factors associated with delivery in a health facility were agreement of partners on the importance of delivering in a health facility and agreement that skills of doctors are better than those of traditional birth attendants. When partners disagreed, the opinion of the woman was more influential in determining delivery-location. Agreement of partners regarding perceptions about the healthcare system appeared to be an important driver of decisions about delivery-location. These findings suggest that both partners should be included in the decision-making process regarding delivery to raise rates of delivery at facility. J Health Popul Nutr 2009 Oct; 27(5):696-703